1999
DOI: 10.3109/10428199909093739
|View full text |Cite
|
Sign up to set email alerts
|

B-Cell Prolymphocytic Leukemia: A Survey of 35 Patients Emphasizing Heterogeneity, Prognostic Factors and Evidence for a Group with an Indolent Course

Abstract: We report a retrospective survey of 35 patients (18 males and 17 females) with B-Prolymphocytic leukemia (B-PLL) followed for a median of 63 months. Twelve patients fulfilled Galton's original clinical and hematological criteria, presented with prominent splenomegaly and hyperleukocytosis and showed rapid progression soon after diagnosis. Twelve cases with gradually increasing spleen size and prolymphocyte count had an indolent course. Seven of this group are alive 68 to 164 months after diagnosis, whereas fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…As in other lymphoid disorders, age, widespread disease and refractoriness to antibody therapy combined with chemotherapy are emerging as unfavorable factors. In a retrospective study that included cases with "smoldering" B-PLL, anaemia and a lymphocyte count greater than 100x10 9 /l were found to be predictors for short survival [10]. Another study confirmed the prognostic impact of anaemia and also age [11].…”
Section: Outcome and Prognostic Factorsmentioning
confidence: 94%
See 1 more Smart Citation
“…As in other lymphoid disorders, age, widespread disease and refractoriness to antibody therapy combined with chemotherapy are emerging as unfavorable factors. In a retrospective study that included cases with "smoldering" B-PLL, anaemia and a lymphocyte count greater than 100x10 9 /l were found to be predictors for short survival [10]. Another study confirmed the prognostic impact of anaemia and also age [11].…”
Section: Outcome and Prognostic Factorsmentioning
confidence: 94%
“…B-PLL is an aggressive disease with median survivals ranging from 3-5 years [4,10,11]. Due to the rarity of the disease, information is limited on the influence of clinical parameters and biomarkers that predict prognosis.…”
Section: Outcome and Prognostic Factorsmentioning
confidence: 99%
“…The clinical course of B-PLL is usually aggressive; however, in some series, an initially indolent disease has been seen in up to 25 % of cases (Shvidel et al 1999 ). Analogous to CLL, alkylation agents such as chlorambucil or even alkylating agent-based poly-chemotherapy, e.g., CHOP, have been used in B-PLL, but efficacy is only modest with response rates < 35 % (Sibbald and Catovsky 1979 ).…”
Section: Conventional Therapy Of B-pllmentioning
confidence: 99%
“…The clinical course is variable and therapy is not indicated in asymptomatic patients. 62 However, B-PLL rarely remains indolent for long, in contrast to stage A CLL. Alkylating agents, such as chlorambucil, are of little value in the management of B-PLL.…”
Section: How I Treat B-pllmentioning
confidence: 99%